Impact of stent retriever diameter on clinical outcomes in mechanical thrombectomy: a multicenter comparison of the 4-mm and 6-mm Solitaire devices - Park, Jung Hyun; Kim, Hoon; Kim, Sunghan (Frontiers in Neurology, 2025)
ObjectiveOptimal stent retriever diameter for mechanical thrombectomy in large vessel occlusion remains debated. We compared the efficacy and safety of Solitaire 4 × 40 mm and 6 × 40 mm stent retrievers in treating distal internal carotid artery (ICA) or middle cerebral artery (MCA) M1 segment occlusion.MethodsWe retrospectively analyzed 145 patients with distal ICA or M1 occlusion treated with the Solitaire 4 × 40 mm (n = 59) or 6 × 40 mm (n = 86) devices. The primary outcome was the rate of first-pass modified thrombolysis in cerebral infarction (mTICI) ≥ 2b without rescue therapy. Secondary outcomes included the number of passes to achieve mTICI ≥2b, device switching and distal embolization rates, and safety parameters.ResultsThe 6 × 40 mm group displayed a significantly higher first-pass mTICI ≥2b rate (58.1% vs. 23.7%, p < 0.001), a lower number of passes to achieve successful revascularization (1.67 ± 1.00 vs. 2.54 ± 1.19, p < 0.001), and lower rates of device switching (4.7% vs. 18.6%, p = 0.015) and distal embolization (8.1% vs. 25.4%, p = 0.009). Postprocedural hemorrhage was less frequent in the 6 × 40 mm group (55.8% vs. 76.3%, p = 0.039), whereas symptomatic hemorrhage rates were similar between the groups (5.8% vs. 5.1%, p > 0.999).ConclusionThe Solitaire 6 × 40 mm stent retriever showed more favorable efficacy outcomes and comparable safety compared to the 4 × 40 mm device for distal ICA or M1 occlusion, suggesting it may be considered a preferred option for these vessels.